Effects of Yakson Therapeutic Touch and Heel Warming on Pain Caused by Heel Stick Procedure, Vital Signs, and Cry Duration in Full-term Neonates - Mahdie Mir; Hamidreza Behnam Vashani; Tahereh Sadeghi; Hasan Boskabadi; Azar Khorshahi (Mashhad University of Medical Sciences, 2018)
Background: Neonates are more sensitive to pain and likely to suffer from its long-term complications. Therefore, various methods including non-nutritive sucking, sensory stimulations, and various supportive interventions are employed to relieve pain in newborns. Aim: This study aimed to compare the effects of Yakson therapeutic touch and heel warming on pain caused by heel stick procedure, vital signs, and cry duration in full-term neonates. Method: This randomized clinical trial was conducted among 78 full-term newborns referred to healthcare centers in Mashhad, Iran, 2017. They were assigned into three groups of Yakson theraputic touch, heel warming using a hot-water bottle with the temperature of 40°C, and control receiving routine care, through randomized block method. Then, vital signs before and after and pain intensity after heel-stick procedure were measured using Neonatal Infant Pain Scale (NIPS). Data analysis was performed using Kruskal-Wallis and Wilcoxon tests in SPSS software, version 16. Results: The study groups were homogeneous considering demographic characteristics. The results of Kruskal-Wallis test showed a significant difference between the groups regarding the mean scores of the NIPS at the post-intervention phase (P=0.02). However, no significant difference was observed between pre- and post-intervention phases in the groups considering respiratory and heart rates. Additionally, cry duration significantly reduced in the group that received Yakson therapeutic touch (P=0.03). Implications for Practice: The use of Yakson therapeutic touch could relieve pain, soothe the neonates, and shorten cry duration in newborns after heel stick procedure. Nevertheless, heel warming only increased up blood flow for easier blood sampling.